Investigação do controle por regras e do controle por histórias de reforço sobre o comportamento humano - ALBUQUERQUE, Luiz Carlos de (2011)
This study investigated the role of experimental history and of relative density of reinforcement on rule following behavior. Sixteen undergraduate students participated. Under a matching-to-sample procedure, with 3 comparison stimuli, the participants were asked to point the comparisons in sequence, according to their dimension, Color, Thickness or Form, in common to the sample. At the beginning of Phases 1, 2, 3 and 4, participants were exposed, respectively, to minimal instructions, a discrepant rule (specifying a non reinforced sequence), a corresponding rule (specifying a TFC sequence) and a repeated discrepant rule. Only the CTF sequence was reinforced in all phases. In Phase 3, two sequences, TFC and CTF, were concurrently reinforced (Concurrent FR 2 FR6 and FR2 FR6). Control by rules and by reinforcement history were both observed, under specific conditions. These findings have implications for drawing a distinction between behaviors controlled by rules and those shaped by contingencies.